ISOLASI DAN KARAKTERISASI ISOLAT KONSORSIUM BAKTERI LAHAN PERTANIAN SEBAGAI POTENSI DEGRADASI PESTISIDA PROPOXUR - Ahmad Qi Sahlan; Endang Kusdiyantini; Sri pujiyanto (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2014)
Propoxur pesticide is a pesticide used widely enough by the Indonesian agricultural community. This pesticide is used as a systemic pesticide in agricultural areas to deal with pests as well as insecticides, herbicides, and bactericide. Study of the degradation of propoxur has long performed using the bacterial bioremediation agent. Bacterial consortium is a combination of several bacteria in a medium which that has a complementary function in the environment. The purpose of this study was the isolation and characterization of a consortium of farms that use propoxur pesticide. Isolation was done by spread plate and was observed characteristics of colony morphology. The obtained isolates were tested against propoxur and its potential role in the consortium. Degradation of propoxur observations using High Performance Liquid Cromatography (HPLC). Isolation results obtained 8 (eight) bacterial isolates and one that have an important role in the consortium is K1 isolate. K1 isolate were able to work up a consortium to degrade Propoxur in 2 isolates with K2 isolate. The interaction of these bacteria are natural and have a tendency to vary in nature after a process of isolation. K1 isolate are not able to work alone in a mineral medium, and worked with synergistic and complementary that in the bacterial consortium. KSR consortium optimum growth occurs in an environment with temperature 35 °C and pH 6.Keywords: Isolation, Propoxur, Bioremediation, Bacterial Consortium, HPLC